The effects of economic and political instability on decentralised secondary schools in Mashonaland Central Province, Zimbabwe: a case study - Katsinde, Tapfuiwa James (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
The purpose of the study was to analyse the effects of economic and political instability on decentralised secondary schools in Mashonaland Central Province, Zimbabwe between 2000 and 2017. Previous studies in Zimbabwe and elsewhere have shown that schools were negatively affected by economic and political instability. This study adds to this literature by using habitus as a conceptual framework. This was a qualitative study which made use of a multi-case research design. Data was collected using focus group discussions, interviews and document analysis. Eight research sites in the form of secondary schools in four districts were used. Data analysis was done using theoretical prepositions guided by research objectives and research questions. Data presentations was characterised by quotes of participants. Trustworthiness based on dependability, credibility, transferability and conformability formed the basis of quality assurance measures. The study revealed that economic and political instability had similar negative results in the field of secondary schools in the province. Economic instability negatively affected school activities which included teaching and learning, administration and development work. In addition economic instability affected individual secondary school actors psychologically. Economic instability affected relations among the secondary school actors by aggravating already existing contestations amongst actors. Similarly, political instability affected secondary school activities such as teaching and learning, school administration, development, donations and social benefits. Secondary school actors were individually affected psychologically and through physical abuse and the way they responded to political instability. The study has shown that decentralised secondary schools found it difficult to solve the problems introduced by economic and political instability especially when the instabilities occurred within the difficulties of the broader Zimbabwean context. It is therefore recommended that decentralised secondary schools should be assisted financially and with resources to withstand economic challenges. There is a need to protect secondary schools from political activities and activists as these have devastating effects on education if allowed to have a free reign. Further similar research is recommended for other provinces in the country.
Keywords: Education, Secondary -- Political aspects -- Zimbabwe; Political violence -- Zimbabwe; Zimbabwe -- Economic conitions -- 1980-; Zimbabwe -- Politics and government -- 1980-